(untitled) (Archives of Criminology, 1964)
The contribution discusses the results of questionnaire polls concerning the consumption of intoxicating drink in Poland. The investigation was carried out by the Centre for Research on Public Opinion attached to the Polish Radio, on the instructions of the Central Social Anti-Alcoholic Committee, in 1961. The investigation has covered a representative sample of the total adult population in Poland, of an age of twenty years and above. The poll, taken throughout the whole country, has comprized, for the total of the country, a sample comprizing 3000 adults, and is representative from the point of view of domicile, sex, age, social and professional group, and education. The basic question of the poll, modelled on the formulation used in the well-known poll carried out by the Finnish Foundation for Research on Alcoholism[2], read: “ When, ,prior to our present conversation, did you last drink any of the following liquors: vodka, wine or beer ? How many days ago was that ? How much did you drink then?” Apart from that basic question, a control question was still introduced: „How many times did you drink alcoholic liquor ………. within three months……….?, as well as: “ How much did you usually drink at any one time during that period?” The basic question, the one dealing with the last one-time consumption of alcohol is of the greatest value of all, as one which appeals to the memory of the person interviewed within a limited period of time. The results obtained on the basis of that question are considerably more reliable than the answers to the control questions, which comprize both a longer period of time and a larger number of facts; in the answers to the latter set of questions the interviewed exhibit a clear tendency to equalize themselves with a certain mean pattern of drinking which is characteristic of the population in question. As far as the questions concerning the frequency of drinking and the average quantities of alcohol consumed at any one time are concerned, use was made, first and foremost, of answers on the basis of the question; in this connection the assumption was accepted — similarly as had been the case with the Finnish investigation — that the period which divided the successive cases of alcohol consumption was, on an average, twice longer than the period dividing such last consumption from the moment of carrying out the interview. Owing to the correlating of the characteristics of the persons investigated from the point of view of the frequency of drinking and of the quantity of alcohol drunk at any one time, mean annual values of the annual consumption of intoxicating drink by the several groups of persons under investigation were established[3]. The representativeness of the total of the results obtained has been checked by calculating the annual consumption per person in the population under investigation as compared with consumption by the total of the population, i. e. the entire adult population of the country. The poll has comprized about 75 to 80 per cent, of the actual consumption of alcohol by the adult population. We suppose that the remaining 20 to 25 per cent, is, to a large extent, drunk by the persons who drink most. Such a supposition is based on the fact that those who carried out the poll could not, for obvious reasons, address themselves to drunken persons. The consumption of alcoholic drink by adult persons in town and country assumes the following proportions per year: Vodka (in litres of absolute alcohol): in the towns — 2.63; in the country — 2.51 Wine (in litres): in the town — 6.46; in the country — 6.18 Beer (in litres) in the town — 27.10; in the country — 23.04 Consequently, the difference between the consumption of intoxicating drink in town and country is very small. Men drink considerably more intoxicating drink than women, both in town and country. The mean consumption of intoxicating drink as per one man and one woman within one year looks as follows: Vodka: men — 11.4 litres; women — 1.99 litre Wine: men — 9.4 litres; women — 3.6 litre Beer: men — 48.0 litres; women — 5.0 litre The consumption of vodka by men and by women respectively assumes the approximate ratio of 6 to 1, and that ratio decides of the ratio of consumption of all kinds of alcoholic drinks, approximately at the ratio of 5 to 1. In the towns men drink four times as much intoxicating drink as women do, and in the country 5.6 times as much. Among the persons interviewed there were 15.7 per cent, of teetotallers who drank no intoxicating drink whatsoever; their percentage was 25.1 among the women, and 7.6 per cent, among the men. Among the women interviewed in the towns the percentage of teetotallers amounted to 21.8 per cent., in the country — to 28.5 per cent, whereas nearly one-half of the women interviewed in the town and in the country did not drink any vodka (44.8 per cent, and 53.6 per cent respectively). Among the men interviewed in towns teetotallers amounted to 7.7 per cent. A quantity of alcohol not exceeding 4 litres of one-hundred-per-cent, spirit per annum is drunk by 44.2 per cent., while 48 per cent, drink more that 4 litres. As they get on in years, the percentage of those drinking up to 4 litres annually increases. Married life favours the diminution of the number of men who drink intensely. Bachelors and divirced men drink more than married men. Among manual workers the percentage of men who drink a great deal is very considerably higher than it is among brain workers. A larger consumption of vodka is closely connected with a larger consumption of wine. The consumption of wine and beer does not take the place of the consumption of vodka, but rather supplements it. The drinking of intoxicating drink by the persons interviewed is fairly evenly distributed throughout all the days of the week, with but a slightly marked increase on Saturdays and Sundays, and a decrease in alcohol consumption on Mondays. In the country the drinking of alcohol is more evenly distributed among the several days of the week than it is in the town. There exists a small group of persons (14,8 per cent.) who drink over 81.1 per cent, of the total amount of vodka. Nearly the same percentage (14.1 per cent.) accounts for 81.2 per cent, of the total quantity of wine. As far as beer is concerned, 33.2 per cent, of the interviewed drinks 97.8 per cent, of the quantity of beer drunk by all the investigated together. 8 per cent, of the interviewed drink more than 12 litres of absolute alcohol per year, as well as drinking 52.3 per cent, of the total quantity of alcohol. When we recalculate that into absolute figures, it appears that, in the country as a whole, about 1,420,000 persons of the age of over twenty years drink more than one-half of the total quantity of alcohol consumed by adults. This is the group of persons, from which habitual alcoholics, as well as persons who commit criminal offences of various kinds while under the influence of drink, are recruited. When analysing the group of men who drink the most, the group in which we have included those men who drink above fifty per cent, of the total quantity of alcoholic drink consumed by the total of the interviewed, we find that: In the towns, the men who drink the most are nearly equally represented in the age group of 20 to 29 years and in the group of older individuals. They are less numerous among brain workers than among manual workers, and relatively less numerous among the men with a lower income. In the country the men who drink most are most numerous in the older age groups (after thirty). A high percentage of men who drink most is to be met with among those who work away from the farm. We may expect to meet more frequently with men drinking intensely in suburban localities and in distant provincial localities, than in localities situated at a medium distance from town. When investigating the data concerning the amounts of alcohol drunk at any one time, we find that more than one-half of the total number of men investigated drink at one time large quantitities of alcohol — about and above a quarter litre of vodka (52.8 per cent, in towns and 55.4 « per cent, in the country) [4]. The highly harmful social effects brought about by the drinking of large quantitites of alcohol at one time have induced the author to introduce a new method of measurement, which serves for an evaluation of the dimensions of intoxication of the organism, caused by alcohol. The author takes as unit of intoxication the presence of one pro mille in weight of alcohol in the blood within one minute, and designates it with the letter eta. The action of alcohol upon the organism and the mind of the drinker is in close relation with the concentration of alcohol in the blood. A certain exiguous quantity of alcohol may be detected in human blood; it is there independently of the consumption of alcoholic drink (the so-called physiological level). That quantity amounts to about 0.03 pro mille. This physiological quanitity has not been taken into account in the evaluation of intoxication unitas. An example of the concentration of alcohol in the blood after the consumption of alcoholic drink has been given in the graph, placed, in the Polish text, on page 319. In this graph, the curve defines the concentration of alcohol in the blood, experimentally found, as well as the time which has elapsed since the moment of drinking (O). The area comprized between the ABC curve and the X axis, minus the area which corresponds to the physiological contents of alcohol in the blood defines the number of units of intoxication suggested by us. The eta unit of intoxication corresponds, in our graph, to the surface of a rectangle whose sides are equal to 0.1 pro mille of alcohol in the blood (in the graph the scale in the ’Y” axis) and ten minutes (in the graph the scale of the “ X” axis. The behaviour of the curve given in the graph changes in dependence on a number of factors. The most important of those factors, and those which it has been attempted to take into consideration in further calculations, are the following: — The quantity of alcohol consumed, — The fact whether such consumption has taken place in the course of having a full meal, or without one, — The period of time which has elapsed from the moment of beginning, to that of finishing, the drinking[5] — The weight of the body of the drinking individuals. For the sake of simplification, in the calculation the area of the A0 B Ct triangle has been taken to be the equivalent of the actual intoxication of the organism, caused by the consumption of alcohol. It has been calculated from the formula: where: B = the maximal alcohol concentration in the blood in weight percentages t = the time (in minutes) which has elapsed from the moment of starting drinking down to the moment of reaching the physiological level of alcohol in the blood. The value of the co-ordinates of the B and Ct points has been calculated with the help of Widmork’s formula. In order to be able to apply the measurements suggested to the comparison of the intoxicatlion of large groups of the population we ought to possess the following data: — The average frequency of the consumption of the several alcoholic beverages; — The average quantity consumed at any one time, — The division of the frequency of consumption, according to whether it took place together with a meal or without one, — The time which has elapsed from the moment of the starting of drinking to the moment of finishing it. Our investigation does not provide an answer to the latter two questions. Neither do we know anything concerning the existence of other research which would define the habits which prevail in Poland in this respect. Consequently we assume the values of both frequency and quantity, which are the values which decide of the result of the calculation, on the basis of the answers obtained. On the other hand, both the fact of alcohol having been taken either with a meal or without, and the time of the duration of the process of consumption have been assumed, for Polish calculations, exclusively on the basis of current observation. The calculations which have been carried out have made it possible to compile an evaluation of the intoxication undergone by men and women, both in town and in the country. The intoxication of the organism (calculated in eta units), brought about by the drinking of one unit of pure alcohol in the form of vodka, is higher in town than in the country by about 20 per cent.; and with women it is higher than with men by about 10 per cent, (this is due to the smaller average weight of the body with women). Group of investigated Eta coefficient 1 litre of Consumption within one Intoxination within one 100 per cent. Alcohol year of absolute alcohol year in thousands of eta Men Vodka Town 806 5.33 4.3 Country 676 5.32 3.6 Women Town 914 1.75 1,6 Country 720 1.29 0,93 Men Wine Town 518 1.91 0,99 Women Beer Town 325 2.52 0,82 One and the same quantity of alcohol, consumed by men living in towns, in the form of wine, causes an intoxication of the organism smaller by about 36 per cent., and in the case of beer — by about 60 per cent, (this is influenced by the smaller dose of pure alcohol drunk at one time). The quantity of pure alcohol in the form of beer drunk by men living in towns constitutes approximately one-half of the quantity of alcohol consumed in the form of vodka. On the other hand, the amount of intoxication of the organism caused by beer is six times lower, for this depends on the amount of pure alcohol drunk at any one time. The suggested unit of measurement, eta, is particularly useful, when with its help we compare populations with altogether different habits connected with the consumption of alcohol, such as e.g. Poland and the Latin countries. The data in our possession make it possible to carry out an interesting comparison with Italy. In spite of the fact that the consumption of alcohol per one man is more than twice higher in Italy than it is in Poland, the amount of intoxication there is less than one-half of that in Poland. One litre of pure alcohol drunk there is tantamount to an intoxication of the organism 5.5 times smaller than is the case in Poland. France is the country where the highest consumption of alcohol throughout the whole world is recorded: 30 litres of absolute alcohol per adult person per year, which means more than five times .more than in Poland. The results of investigation available do not make it possible directly to evaluate the amount of intoxication in France. Since, however, the habits concerning alcohol consumption there are similar to those of Italy, we may apply the same coefficient of intoxication per one litre of pure alcohol as we have done in the case of Italy. This leads us to the conclusion that the amount of the intoxication of the organism in France is about 3500 eta per year and per adult person, and consequently that it is lower than in Poland. As results from the data concerning the dimensions of intoxication when drinking distilled alcoholic beverages in large quantitites, the harmful social effects here must be considerably larger than they are when alcohol is being drunk in the form of even larger quantitities, but of low-percent-age alcoholic beverages, drunk every day, but in small doses. [1] The results of the questionnaire research discussed concern the period of the relatively smallest consumption of alcoholic drink in Poland (February and March); the average daily sales of alcohol in this period amount to about 87 per cent, of the daily sales throughout the whole of the year. [2] Pekka Kuusi: “Alcohol Sales Experiment in Rural Finland” — The Finnish Foundation for Alcohol Studies, 1957. [3] A detailed discussion of the application of the method of research and of statistical elaboration is contained in Dr A. Święcickie contribution „Wyniki badań nad spożyciem alkoholu w Polsce” (The Results of Research on the Comsumption of Alcohol in Poland”. Ośrodek Badania Opinii Publicznej (Centre of Research on Public Opinion), Warsaw 1962. [4] As far as wine and beer are concerned, the prevailing custom in Poland is a moderate consumption of those alcoholic drinks at any one time. [5] The expression of “ one case of drinking” is meant to include a number of consumptions (acts of swallowing), the lapse of time between which has been too short to allow alcohol concentration in the blood to sink to its psysiological level,